Preparation method of high-strength high-barrier saline-alkaline-tolerant biodegradable mulching film
By modifying the alkali resistance, hydrophobicity and degradation speed of biodegradable materials, the problems of poor stability and rapid degradation rate of existing mulch films in alkaline environments can be solved, and high-strength, high barrier and adjustable biodegradable mulch films are achieved, which are suitable for a variety of crops and soil environments.
Patent Information
- Application Number
- CN202510074913.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing biodegradable plastic films have poor stability, insufficient mechanical strength, poor barrier performance and too fast degradation rate in alkaline environments, making it difficult to meet the coating needs of long crops and saline-alkali land.
Through the modification project, alkali-resistant additives, hydrophobic materials, thermoplastic starch particles and nanomaterials are used to improve the strength, barrier properties and degradation speed adjustment of the material. Specific steps include bamboo powder surface modification, starch thermoplastication, blend granulation and blown film bidirectional stretching.
It achieves high-strength, high barrier and adjustable biodegradable plastic film, which is suitable for different soil environments and crop needs, reduces material costs, and degrades quickly and safely after use, and the product is soil-friendly.
Abstract
Description
Technical Field
[0001] The present invention specifically relates to the technical field of preparation of degradable mulch films, and in particular is a method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film. Background Art
[0002] Since the 1980s, China has been using plastic mulch in the agricultural field for about 40 years. During this period, a considerable amount of plastic fragments and particles have accumulated in the soil every year, causing the soil structure to be destroyed and becoming compacted. The roots of crops have encountered many difficulties in absorbing water and nutrients. The resulting crop yield reduction problem has become increasingly serious, and the white pollution control work caused by agricultural mulch films is urgent. Since 2019, many domestic manufacturers have devoted themselves to the research and development and production of new biodegradable plastic mulch films. Such mulch films with PBAT, PLA, PPC, and PHA as substrates have brought new hope for alleviating the dilemma of agricultural mulch film pollution. However, this type of degradable plastic mulch film also has many problems. On the one hand, its high material cost makes large-scale promotion and application face cost pressure; on the other hand, due to the inherent characteristics of its own materials, it has defects such as poor mechanical strength, insufficient barrier properties, and too fast degradation rate. In actual use, these disadvantages are manifested in the high difficulty of mechanical film laying operations and the unsatisfactory water and moisture retention effects. Although some of the above problems can be improved to a certain extent by means of the blending process of different materials and the strengthening and toughening technology, they still cannot be solved fundamentally.
[0003] What is particularly critical is that these materials all have a fatal shortcoming, that is, the ester group on their molecular chain has poor stability and is extremely vulnerable to attack by external factors. In an alkaline environment, the attack of hydroxyl groups can easily trigger a hydrolysis reaction, and the reaction is irreversible. The random breakage of the ester bond leads to the breakage of the molecular chain. In addition, due to the continuous action of external forces such as wind, thunder, lightning, rain, and hail in nature, the biodegradable mulch currently on the market can only meet the use needs of crops with short growth cycles such as beets and peanuts. For crops with long growth cycles such as cotton, as well as saline-alkali and semi-saline-alkali lands with high pH values, the demand for mulch during the crop production period cannot be effectively met. Summary of the invention
[0004] To this end, the present invention first analyzes the disintegration and degradation mechanism of biodegradable materials from the perspective of molecular structure, and summarizes several key factors affecting the disintegration and subsequent degradation of materials:
[0005] 1. The influence of light, oxygen, heat and mechanical forces in nature (molecular chain breakage);
[0006] 2. Influence of soil alkaline environment (easy to be attacked by hydroxyl groups);
[0007] 3. The influence of moisture (hydrolysis reaction);
[0008] 4. Microbial influence;
[0009] 5. The influence of the molecular weight of the material and the instability of the ester group in the molecular structure.
[0010] In view of the above influencing factors, the present invention systematically improves the material modification engineering, specifically including:
[0011] 1. Evaluate the alkali resistance of various additives to be used in advance to improve the applicability of composite materials in alkaline environments;
[0012] 2. Use alkali-resistant and environmentally friendly additives to modify the material to be antioxidant, heat-resistant, and UV-resistant, and use nanomaterial filling and moderate cross-linking modification to improve the material strength and water vapor barrier properties;
[0013] 3. Use hydrophobic materials as much as possible, or make hydrophobic modifications to hydrophilic main materials, fillers and additives to minimize the impact of moisture on material stability;
[0014] 4. Hydrophobic thermoplastic starch granules TPS are used as degradation rate regulators, in which urea is included in the plasticizer, which has good plasticizing effect and is not easy to regenerate. Starch has stable performance in the early stage as a filling and cost-reducing reinforcing material. In the later stage, under external force damage and after the volatilization of urea, it becomes a microbial enrichment point that induces biological degradation; that is, the physical properties of the entire material collapse through the biological degradation of starch, causing a large number of end groups to be exposed, thereby accelerating starch degradation. The present invention cleverly increases or decreases the microbial enrichment attack points by adjusting the proportion of TPS in the composite material, so that the biodegradation rate can be adjusted after the mulch film is disintegrated after use;
[0015] 5. Chain extender and hyperbranched polyester are used together to synergistically increase the average molecular weight of the blend and reduce the risk of rapid attenuation of material stability caused by rapid molecular chain breakage and molecular weight decline;
[0016] 6. The nanomaterial is first dispersed in the plasticizer, then filled in the bamboo powder, and finally the modified bamboo powder is blended with the main substrate. In this way, the nanomaterial is dispersed three times in the whole process, the dispersion is more uniform, the agglomeration phenomenon is greatly reduced, and the overall modification effect is better than that of a single dispersion method;
[0017] 7. Adding materials such as bio-based bamboo powder, bio-based polycaprolactam and bio-based thermoplastic starch can improve the overall bio-based content while improving quality and reducing costs, and can reduce the proportion of ester-based materials in the composite material to slow down the rapid degradation of the material in an alkaline environment;
[0018] 8. The use of polarizer not only reduces the damage caused by ultraviolet radiation to the film, but also increases the light transmittance, which is beneficial to plant growth and increases production.
[0019] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film, which comprises the following steps:
[0020] Step 1: Surface modification of bamboo powder:
[0021] 600-1000 mesh bamboo powder, 20-25% of the bamboo powder mass percentage, is soaked with 8% NAOH solution for 2 hours, and then hydrophobic micro-nano material, maleic anhydride, glycerol, and hyperbranched polyester are added in sequence with high-speed stirring, and the temperature is raised to 105° C. and then stopped for about 35 minutes, and then dried with hot air for use;
[0022] Step 2: Thermoplasticization and hydrophobic modification of starch:
[0023] 65-90 parts of starch, 10-45 parts of composite plasticizer, 0.1-5 parts of alkali-resistant surfactant, 0.1-5 parts of cross-linking agent and esterifying agent are mixed and granulated by a twin-screw extruder for later use;
[0024] Step 3: Blending and granulation:
[0025] After the basic biodegradable materials, nanomaterials, BF, TPS, lignin, polarizing agent, chain extender and PVB are fully mixed in a high-speed mixer, they are granulated with low energy consumption and high output through a double-stage extruder combined with a single screw and a twin screw;
[0026] Step 4: Finished product after biaxial stretching of film blowing:
[0027] The granulated material is subjected to a film blowing process and subjected to a biaxial stretching operation in a specific film blowing equipment to obtain a finished biodegradable mulch film.
[0028] Further, preferably, in step 3, the basic biodegradable material is one or more of PBAT, PLA, PPC, and PHA.
[0029] Further, preferably, in step 3, blending is performed in a ratio of PBAT:PPC:nanomaterial:BF:TPS:{lignin+polarizer+chain extender+PVB}=55:20:1~3:20:1~5:3~6.
[0030] Furthermore, preferably, in step 1, the micro-nano material is at least one of nano-calcium carbonate, nano-silicon dioxide, carbon nanotubes, nano-montmorillonite, nano-barium sulfate, graphene, nano-zinc oxide, and nano-calcium hydroxide.
[0031] Further, preferably, in step 2, the alkali-resistant surfactant is one or more of anionic alkali-resistant surfactant or nonionic alkali-resistant surfactant.
[0032] Further, preferably, in step 2, the cross-linking agent is one or more of an organic cross-linking agent or an inorganic cross-linking agent.
[0033] Further, preferably, in step 2, the esterification agent includes a coupling agent, sodium trimetaphosphate, and stearic acid, wherein the coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
[0034] Furthermore, preferably, in step 2, a rheological agent may be added, wherein the rheological agent is one or more of an organic rheological agent or an inorganic rheological agent.
[0035] Furthermore, preferably, in step 3, TPS is a hydrophobic degradation cycle regulator, and is obtained by hydrophobically modifying ordinary TPS.
[0036] The present invention adopts the above technology and has the following beneficial effects compared with the existing technology:
[0037] 1. The present invention takes into account cost optimization, performance improvement and environmental friendliness, improves the applicability of the material in an alkaline environment, and can be quickly degraded after use, and the degradation products are friendly to the soil environment; laying biodegradable mulch in saline-alkali land and semi-saline-alkali land has obvious effects on increasing crop yields and has huge potential; the promotion and application of the technology of the present invention has important strategic significance for opening up a second backup granary for the Chinese people outside the 1.8 billion mu of arable land red line.
[0038] 2. This technology is still based on different biodegradable materials such as PBAT / PLA / PPC / PHA, and the performance of the materials is complemented by blending and modification. Two-dimensional micro-nano materials with aspect ratio and high specific surface area are used as heat-resistant reinforcement and barrier materials. The surface of bamboo powder is modified by special process as cost-reducing filler and toughening reinforcement. Alkali-resistant surfactants, cross-linking agents, coupling agents and penetrants are used as comprehensive modification aids. Hydrophobic modified thermoplastic starch is used as degradation rate regulator. Lignin, polarizing agent and the like are used as anti-ultraviolet (variable) agents. Finally, a two-stage extruder combined with single screw and twin screw is used for low-energy consumption and high-output granulation, and the final product is prepared through film blowing process. DETAILED DESCRIPTION
[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0040] Embodiment: The present invention provides a technical solution: a method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film, which comprises the following steps:
[0041] Step 1: Surface modification of bamboo powder:
[0042] 600-1000 mesh bamboo powder, 20-25% of the bamboo powder mass percentage, is soaked with 8% NAOH solution for 2 hours, and then hydrophobic micro-nano material, maleic anhydride, glycerol, and hyperbranched polyester are added in sequence with high-speed stirring, and the temperature is raised to 105° C. and then stopped for about 35 minutes, and then dried with hot air for use;
[0043] It should be added that the nanomaterials are uniformly dispersed in the liquid plasticizer by ultrasonic method in advance, and the nanoparticles and liquid plasticizer evenly penetrate into the bamboo powder to enhance the plasticizing effect;
[0044] Wherein, preferably, the liquid plasticizer is at least one of silicone oil, glycerin, epoxidized vegetable oil, citrate plasticizer, and polyol benzoate;
[0045] It should be noted that the use of hyperbranched polyester to adjust the melt flow rate of the bamboo powder system in advance can also increase the average molecular weight of the entire blended material during the final granulation, thereby improving the material stability;
[0046] Step 2: Thermoplasticization and hydrophobic modification of starch:
[0047] 65-90 parts of starch, 10-45 parts of composite plasticizer, 0.1-5 parts of alkali-resistant surfactant, 0.1-5 parts of cross-linking agent and esterifying agent are mixed and granulated by a twin-screw extruder for later use;
[0048] Preferably, the composite plasticizer is urea (formamide), soybean oil, caprolactam, and water in a ratio of 20:20:15:45. Starch, plasticizer, and various additives are added in a high-stirring machine in sequence. After extrusion by a twin-screw extruder, the temperature is controlled below 90 degrees and pelletized by hot cutting on the die surface, and then dried with cold air for standby use.
[0049] Step 3: Blending and granulation:
[0050] After the basic biodegradable materials, nanomaterials, BF, TPS, lignin, polarizing agent, chain extender and PVB are fully mixed in a high-speed mixer, they are granulated with low energy consumption and high output through a double-stage extruder combined with a single screw and a twin screw;
[0051] It should be noted that hyperbranched polyester significantly increases the average molecular weight of the entire blend system and improves the stability of material properties;
[0052] Step 4: Finished product after biaxial stretching of film blowing:
[0053] The granulated material is subjected to a film blowing process and subjected to a biaxial stretching operation in a specific film blowing equipment to obtain a finished biodegradable mulch film.
[0054] In this embodiment, in step 3, the basic biodegradable material is one or more of PBAT, PLA, PPC, and PHA.
[0055] In this embodiment, in step 3, blending is performed in a ratio of PBAT: PPC: nanomaterial: BF: TPS: {lignin + polarizer + chain extender + PVB} = 55: 20: 1~3: 20: 1~5: 3~6.
[0056] In this embodiment, in step 1, the micro-nano material is at least one of nano calcium carbonate, nano silicon dioxide, carbon nanotube, nano montmorillonite, nano barium sulfate, graphene, nano zinc oxide, and nano calcium hydroxide.
[0057] In this embodiment, in step 2, the alkali-resistant surfactant is one or more of anionic alkali-resistant surfactant or nonionic alkali-resistant surfactant.
[0058] In this embodiment, in step 2, the cross-linking agent is one or more of an organic cross-linking agent or an inorganic cross-linking agent.
[0059] In this embodiment, in step 2, the esterification agent includes a coupling agent, sodium trimetaphosphate, and stearic acid, wherein the coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
[0060] In this embodiment, in step 2, a rheological agent may be further added, and the rheological agent may be one or more organic rheological agents or inorganic rheological agents.
[0061] In this embodiment, in step 3, TPS is a hydrophobic degradation cycle regulator, and is prepared by hydrophobic modification of ordinary TPS.
[0062] In specific implementation, the present invention provides the following three embodiments:
[0063] Embodiment 1:
[0064] The first step is the surface modification of bamboo powder:
[0065] Select 800 mesh bamboo powder, soak it with 8% NaOH solution for 2 hours according to the mass percentage of bamboo powder of 22%. Then add hydrophobic nano-silica, maleic anhydride, glycerol, and hyperbranched polyester in turn for high-speed stirring. During the stirring process, the temperature is raised to 105°C and then stopped, which lasts for about 35 minutes. Among them, nano-silica is uniformly dispersed in glycerol in advance by ultrasonic method to promote its uniform penetration into the interior of bamboo powder to enhance the plasticizing effect. After that, it is dried by hot air for standby use, and the proportion of each component is according to BF: glycerol: SiO2: maleic anhydride: HPUER = 70:21:5:2:2.
[0066] The second step is the thermoplastic treatment and hydrophobic modification of starch:
[0067] Weigh 75 parts of starch, 25 parts of composite plasticizer (urea (formamide), soybean oil, caprolactam, water are mixed in a ratio of 20:20:15:45), 2 parts of alkali-resistant surfactant, and 2 parts of crosslinking agent (silane coupling agent, sodium trimetaphosphate, stearic acid). Add starch, plasticizer and various additives in a high-speed mixer in turn, extrude through a twin-screw extruder, control the temperature below 90 degrees, cut into pellets by hot cutting on the die surface, and then dry with cold air for use.
[0068] The third step is blending and granulation:
[0069] Blend according to the ratio of PBAT:PPC:PHA:nanomaterial:BF:TPS:{lignin, polarizer, chain extender, PVB}=55:20:5:2:20:3:3. Among them, PBAT is 55 parts, PPC is 20 parts, bamboo powder is 20 parts, TPS is 3 parts, chain extender, compatibilizer, crosslinker, anti-ultraviolet agent (or polarizer) are 0.5 parts each (the exact amount can be determined according to the specific materials actually selected). After the above raw materials are fully mixed in a high-speed mixer, they are granulated with low energy consumption and high output through a double-stage extruder combined with a single screw and a twin screw.
[0070] Step 4: Finished product after biaxial stretching of film blowing:
[0071] The material obtained by granulation is subjected to a film blowing process and subjected to a film blowing biaxial stretching operation in a specific film blowing equipment to obtain a finished biodegradable ground film.
[0072] Embodiment 2:
[0073] The first step is the surface modification of bamboo powder:
[0074] 600 mesh bamboo powder was used, and 20% of the bamboo powder by mass was soaked in 8% NaOH solution for 2 hours. Then, nano calcium carbonate, maleic anhydride, glycerol, and hyperbranched polyester were added in sequence and stirred at high speed, and the temperature was raised to 105°C and maintained for 35 minutes. Nano calcium carbonate was pre-ultrasonic dispersed in silicone oil and then mixed with other substances. The treated bamboo powder was hot-air dried for use, and the ratio was BF: glycerol: nano calcium carbonate: maleic anhydride: HPUER = 70:21:4:2:3.
[0075] The second step is the thermoplastic treatment and hydrophobic modification of starch:
[0076] Take 65 parts of starch, 35 parts of composite plasticizer (urea (formamide), soybean oil, caprolactam, water = 20:20:15:45), 1 part of alkali-resistant surfactant, 1 part of cross-linking agent (silane coupling agent, sodium trimetaphosphate, stearic acid) and blend. Add the raw materials in a high-speed mixer in sequence, extrude through a twin-screw extruder, control the temperature below 90 degrees, hot-cut the pellets on the die surface, and then dry them with cold air for later use.
[0077] The third step is blending and granulation:
[0078] Blend in the ratio of PBAT:PPC:PBS:nanomaterial:BF:TPS:{lignin, polarizer, chain extender, PVB}=55:20:3:1:20:1:6. PBAT 55 parts, PPC 20 parts, bamboo powder 20 parts, TPS 1 part, chain extender, compatibilizer, crosslinker, anti-ultraviolet agent (or polarizer) 0.3 parts each. After mixing evenly, granulate through a double-stage extruder.
[0079] Step 4: Finished product after biaxial stretching of film blowing:
[0080] The granulated product is biaxially stretched by the film blowing process to produce the finished biodegradable mulch film.
[0081] Embodiment 3:
[0082] The first step is the surface modification of bamboo powder:
[0083] Select 1000 mesh bamboo powder, soak it in 8% NaOH solution for 2 hours at 25% of the bamboo powder mass percentage, then add nano-montmorillonite, maleic anhydride, glycerol, and hyperbranched polyester and stir at high speed, heat to 105°C and keep for 35 minutes, nano-montmorillonite is ultrasonically dispersed in epoxidized vegetable oil and then participates in the reaction, the treated bamboo powder is hot-air dried for use, the ratio BF: glycerol: nano-montmorillonite: maleic anhydride: HPUER = 70:21:6:2:1.
[0084] The second step is the thermoplastic treatment and hydrophobic modification of starch:
[0085] Prepare 90 parts of starch, 10 parts of composite plasticizer (urea (formamide), soybean oil, caprolactam, water = 20:20:15:45), 5 parts of alkali-resistant surfactant, 5 parts of cross-linking agent (silane coupling agent, sodium trimetaphosphate, stearic acid) for blending. After mixing in a high-speed stirrer, extrude through a twin-screw extruder, control the temperature below 90 degrees, hot-cut pellets on the die surface, and then dry with cold air for later use.
[0086] The third step is blending and granulation:
[0087] Blend in the ratio of PBAT:PPC:PHA:nanomaterial:BF:TPS:{lignin, polarizer, chain extender, PVB}=55:20:1:3:20:5:3. PBAT 55 parts, PPC 20 parts, bamboo powder 20 parts, TPS 5 parts, chain extender, compatibilizer, crosslinker, anti-ultraviolet agent (or polarizer) 1 part each. Granulate by double-stage extruder.
[0088] Step 4: Finished product after biaxial stretching of film blowing:
[0089] Finally, the finished biodegradable mulch film is obtained by biaxial stretching through a film blowing process.
[0090] The present invention also provides the following 3 comparative examples:
[0091] Comparative Example 1:
[0092] The first step is the surface modification of bamboo powder:
[0093] 800-mesh bamboo powder without special surface modification (i.e., without soaking in NaOH solution and subsequent treatment steps such as adding nanomaterials) is directly used and mixed with other raw materials in proportion.
[0094] The second step is the thermoplastic treatment and hydrophobic modification of starch:
[0095] The treatment was carried out according to the types and amounts of starch, composite plasticizer, alkali-resistant surfactant and cross-linking agent in Example 1, but without hydrophobic modification.
[0096] The third step is blending, granulation and finished product preparation:
[0097] The mixture was blended in the ratio of PBAT:PPC:PHA:bamboo powder:TPS:{lignin, polarizer, chain extender, PVB}=55:20:5:20:3:3 (bamboo powder was untreated), and the finished product was made by film blowing and biaxial stretching after granulation by a two-stage extruder. This comparative example was used to compare the effects of bamboo powder surface modification and starch hydrophobic modification on material properties.
[0098] Comparative Example 2:
[0099] The first step is the surface modification of bamboo powder:
[0100] The bamboo powder surface modification method in Example 1 was used, but without adding hyperbranched polyester.
[0101] The second step is the thermoplastic treatment and hydrophobic modification of starch:
[0102] The starch treatment method in Example 1 was adopted.
[0103] The third step is blending, granulation and finished product preparation:
[0104] The mixture was blended in the ratio of PBAT:PPC:PHA:nanomaterial:BF:TPS:{lignin, polarizer, chain extender, PVB}=55:20:5:2:20:3:3 (BF is bamboo powder without hyperbranched polyester treatment), and the finished product was made by granulation in a two-stage extruder and then film blowing and biaxial stretching. This comparative example is used to compare the effect of hyperbranched polyester on the performance stability of the entire blending system.
[0105] Comparative Example 3:
[0106] The first step is the surface modification of bamboo powder:
[0107] The bamboo powder surface modification method in Example 1 was used.
[0108] The second step is the thermoplastic treatment and hydrophobic modification of starch:
[0109] The starch treatment method in Example 1 was adopted, but urea (formamide) was not added to the composite plasticizer.
[0110] The third step is blending, granulation and finished product preparation:
[0111] The mixture was blended in the ratio of PBAT:PPC:PHA:nanomaterial:BF:TPS:{lignin, polarizer, chain extender, PVB}=55:20:5:2:20:3:3 (TPS is starch without urea (formamide) treatment), and the finished product was made by granulation in a two-stage extruder and biaxial stretching of film. This comparative example is used to compare the effect of urea (formamide) in the thermal plasticization of starch on the material properties.
[0112] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film, characterized in that: It includes the following steps: Step 1: Surface modification of bamboo powder: 600-1000 mesh bamboo powder, 20-25% of the bamboo powder mass percentage, is soaked with 8% NAOH solution for 2 hours, and then hydrophobic micro-nano material, maleic anhydride, glycerol, and hyperbranched polyester are added in sequence with high-speed stirring, and the temperature is raised to 105° C. and then stopped for about 35 minutes, and then dried with hot air for use; Step 2: Thermoplasticization and hydrophobic modification of starch: 65-90 parts of starch, 10-45 parts of composite plasticizer, 0.1-5 parts of alkali-resistant surfactant, 0.1-5 parts of cross-linking agent and esterifying agent are mixed and granulated by a twin-screw extruder for later use; Step 3: Blending and granulation: After the basic biodegradable materials, nanomaterials, BF, TPS, lignin, polarizing agent, chain extender and PVB are fully mixed in a high-speed mixer, they are granulated with low energy consumption and high output through a double-stage extruder combined with a single screw and a twin screw; Step 4: Finished product after biaxial stretching of film blowing: The granulated material is subjected to a film blowing process and subjected to a biaxial stretching operation in a specific film blowing equipment to obtain a finished biodegradable mulch film.
2. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 1, characterized in that: In step 3, the basic biodegradable material is one or more of PBAT, PLA, PPC, and PHA.
3. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 2, characterized in that: In step 3, blending is performed in a ratio of PBAT: PPC: nanomaterial: BF: TPS: {lignin+polarizer+chain extender+PVB}=55:20:1~3:20:1~5:3~6.
4. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 1, characterized in that: In step 1, the micro-nano material is at least one of nano calcium carbonate, nano silicon dioxide, carbon nanotube, nano montmorillonite, nano barium sulfate, graphene, nano zinc oxide, and nano calcium hydroxide.
5. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 1, characterized in that: In step 2, the alkali-resistant surfactant is one or more of anionic alkali-resistant surfactants or nonionic alkali-resistant surfactants.
6. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 1, characterized in that: In step 2, the cross-linking agent is one or more of an organic cross-linking agent or an inorganic cross-linking agent.
7. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 1, characterized in that: In step 2, the esterification agent includes a coupling agent, sodium trimetaphosphate, and stearic acid, wherein the coupling agent is one or more of a silane coupling agent and a titanate coupling agent.
8. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 1, characterized in that: In step 2, a rheological agent may also be added, and the rheological agent may be one or more organic rheological agents or inorganic rheological agents.
9. The method for preparing a high-strength, high-barrier, salt-alkali-resistant biodegradable mulch film according to claim 1, characterized in that: In step 3, TPS is a hydrophobic degradation cycle regulator, and is prepared by hydrophobic modification of ordinary TPS.